The Anesthesiologist and Artificial Intelligence - Hermandez-Cortez, Enrique (2024)
Artificial intelligence has been defined as the study of algorithms, which give machines the ability to reason and perform functions, such as problem solving, object and word recognition, inference of world states, and decision making. The adaptation of AI algorithms and tools to science has brought about a promising future in anesthesiology, offering great potential that must be harnessed by all professionals. Anesthesiology is well positioned to benefit from advances in AI; multiple elements of clinical care, including perioperative and intensive care, pain management and medication administration, medical records, laboratory results, hemodynamic monitoring, ventilatory system, depth of unconsciousness and nociceptive control, images and clinical information, to generate predictive models. Optimize treatment strategies and improve patient safety, allowing the anesthesiologist to focus on overall analysis and decision making.